Screening for congenital hypothyroidism and the association of congenital hypothyroidism with screening thyroid-stimulating hormone levels of 10–20 mIU/L among inborn neonates in a government tertiary care hospital of North Kerala - Jacob, Ambili Susan; Gopinath, Reetha; Divakaran, Binoo (Indian Journal of Child Health, 2019)
Background: Newborn screening for hypothyroidism is necessary because of the high incidence of congenital hypothyroidism (CH) in various studies. The necessity of doing confirmatory tests with screening thyroid-stimulating hormone (TSH) levels as low as 10 mIU/L is still unclear. Objectives: To find out the incidence of CH as well as its association with screening TSH levels between 10 and 20 mIU/L. Materials and Methods: In a prospective observational study, inborn neonates irrespective of their gestational age were enrolled and screened for CH using venous TSH levels. Those with TSH levels ?10 mIU/L were subjected to confirmatory tests (free T4 and TSH levels) for the diagnosis based on the recommendations of the Indian Society for Pediatric and Adolescent Endocrinology. The various characteristics of the neonates such as birth weight, gender, gestational age, and maternal thyroid status were recorded and their relationship with subsequent CH was studied. The association between screening TSH levels 10–20 mIU/L and CH was also analyzed, and the cutoff point for screening TSH was determined using receiver operated characteristic (ROC) curve. Results: A total of 2407 neonates were screened for CH, out of which 357 (14.8%) were retested with free T4 and serum TSH levels. The incidence of CH was 1 in 160.5 (6.2/1000 live births). The male to female ratio was 1.5:1. There was a significant association between screening TSH levels and CH. A total of 0.6% of neonates diagnosed with CH had screening TSH levels in the range of 10–20 mIU/L, but this association was not found to be statistically significant, and the ideal cutoff value was 19.45 mIU/L based on ROC curve. Conclusion: The incidence of CH is high which upholds the need for universal newbornthyroid screening. Although there is no statistically significant association between CH and screening TSH levels 10–20 mIU/L, a few cases are likely to be missed on using a higher screening TSH cutoff value of 20 mIU/L.